STIGMA RECEPTIVITY AND POLLEN VIABILITY OF Melaleuca alternifolia - Baskorowati, Liliana (Secretariat of Forestry Research and Development Agency, 2009)
Stigma receptivity based on seed set and pollen tubes growth following controlled pollination of flowers of different ages was examined in Melaleuca alternifolia. The stigma secretion during 10 days after anthesis and pollen viability under three different temperatures and five storage times were also observed. These series of research were undertaken because successful controlled pollination of M. alternifolia depends on the application of viable pollen to the receptive compatible stigma. The objective of this research was therefore to determine the stigma receptivity and pollen viability of M. alternifolia. Results showed that the stigma receptivity began to develop on day one and finished on day seven after anthesis, peak receptivity occurred from day three to day six. The stigma receptivity also coincides with the appearance of secretion in the stigma, occurring from day three to day seven after anthesis. Therefore, the time for pollination of M. alternifolia appeared to extend for approximately 7 days after anthesis. Data for M. alternifolia showed that regardless of storage temperature, pollen was still viable after 26 weeks of storage; results also demonstrated that the lowest temperature (-18oC) was the best regime for long term storage.